Rates of undiagnosed attention deficit hyperactivity disorder in London drug and alcohol detoxification units - Huntley, Zoe (BioMed Central, 2012)
BACKGROUND: ADHD is a common childhood onset mental health disorder that persists into adulthood in two-thirds of cases. One of the most prevalent and impairing comorbidities of ADHD in adults are substance use disorders. We estimate rates of ADHD in patients with substance abuse disorders and delineate impairment in the co-morbid group. METHOD: Screening for ADHD followed by a research diagnostic interview in people attending in-patient drug and alcohol detoxification units. RESULTS: We estimated prevalence of undiagnosed ADHD within substance use disorder in-patients in South London around 12%. Those individuals with substance use disorders and ADHD had significantly higher self-rated impairments across several domains of daily life; and higher rates of substance abuse and alcohol consumption, suicide attempts, and depression recorded in their case records. CONCLUSIONS: This study demonstrates the high rates of untreated ADHD within substance use disorder populations and the association of ADHD in such patients with greater levels of impairment. These are likely to be a source of additional impairment to patients and represent an increased burden on clinical services.